Розробка web-додатку «доставка суші» - Коваль, О. О. (ХНУРЕ, 2024)
This work is devoted to the development of a sushi delivery system. The report developed the server and client parts of the system for viewing and ordering delivery. Using the system, users can create their own account, manage their personal data, create and edit orders, view a catalog of delivery items, and can also select a delivery route. The development and implementation of the described sushi delivery system has a high chance of success with clear implementation of the assigned tasks and effective risk management.
Keywords: веб-додаток; доставка суші